Implementation of the Khidmah Program in Strengthening the Social Character of Islamic Boarding School Students - Beny Sintasari; Moch. Sya’roni Hasan; Amalia Maghfiroh; Humairourrohmah binti Mastor (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2026)
This study examines the implementation of a pesantren community service program and its role in shaping students’ social character at Pondok Pesantren Abdul Hadi Diwek Jombang. Using a qualitative descriptive approach, the research explores how community service (khidmah) functions as a practical strategy for character education in Islamic boarding schools. Data were collected through in-depth interviews, observation, and documentation involving pesantren leaders, madrasah administrators, and students participating in the community service program. The data were analysed using an interactive qualitative analysis model, while data credibility was ensured through triangulation of sources and methods. The findings indicate that the community service program is systematically implemented through educational activities and pesantren services, such as teaching at Madrasah Diniyah and managing the pesantren cooperative. These activities contribute significantly to the formation of students’ social character, including responsibility, social care, cooperation, tolerance, and service ethics. Direct involvement in real social roles enables students to internalize Islamic values through continuous practice rather than normative instruction alone. Leadership exemplified by the pesantren leader and a strong communal culture are identified as key supporting factors in the program's effectiveness. This study contributes to the discourse on pesantren-based character education by positioning community service as a structured and applicable pedagogical approach for developing students’ social character. However, this research is limited to a single pesantren context, suggesting the need for future comparative and longitudinal studies.